Exploring the intersectionality of stigma and substance use help-seeking behaviours among lesbian, gay, bisexual, transgender, queer, questioning or otherwise gender or sexuality minority (LGBTQ+) individuals in the United States: A scoping review - Yitong Xin; Corrine M. Schwarting; Mary R. Wasef; Alan K. Davis (Taylor & Francis Group, 2023)
ABSTRACTProblematic substance use (SU) is a significant issue among LGBTQ+ individuals, but rates of treatment/help-seeking in this population remain low. This review aimed to investigate literature about intersectional stigma of SU and LGBTQ+ identity and its impact on SU help-seeking behaviours in the U.S. Eligible studies from eight-database were included if peer-reviewed, in English, from the U.S., published between 2000 and 2022, focused on SU, stigma, SU help-seeking behaviours, among LGBTQ+ adults. Of 458 search results, 50 underwent full-text review, 12 were included in the final sample. Minority Stress Theory emerged as a relevant theoretical framework. Findings revealed that increased SU as a coping strategy was associated with minority stress. Intersectional stigma negatively impacted SU treatment experience among LGBTQ+ individuals, leading to avoidance of help-seeking or poor treatment outcomes. Patterns of SU and impact of stigma among LGBTQ+ individuals differ, wherein bisexual and transgender individuals reported significantly more treatment barriers and unique stressors. LGBTQ+ individuals reported earlier age of SU onset and were more likely to encounter opportunities for SU. This review highlights the impact of intersectional stigma on SU help-seeking behaviour among LGBTQ+ individuals in the U.S. Recommendations are provided for future clinical practice, research, and policy to better support LGBTQ+ individuals.